THE SCIENTIFIC RUPTURE: ITS STAGES AND IMPORTANCE IN THE COURSE OF SCIENTIFIC RESEARCH - Abdelkarim Belazzoug; Hamza Djahnit; Zitouni Aiboud; Amara Boudjemaa (International Journal of Innovative Technologies in Social Science, 2025)
The scientific rupture is the initial phase in scientific research, from which the researcher begins constructing their research project. It represents a preliminary stage through which the researcher acquires a clear understanding of the research subject and progressively eliminates previous judgments and misconceptions. It thus constitutes the initial formative action in the research trajectory, facilitating a practical starting point for the researcher’s work. The scientific rupture comprises three essential steps: formulating the initial question, conducting exploratory work, and defining the research problem. After posing the research project as an initial question, the researcher proceeded to investigate and seek specific information related to the topic under study. On the basis of these findings, the researcher develops a theoretical approach to the research subject, constructing the research problem meticulously and systematically. This process follows a rigorous methodology, becoming progressively more detailed from one stage to the next, resembling a funnel that transitions from the general to the specific and then to the most specific.